2021
DOI: 10.2196/24110
|View full text |Cite
|
Sign up to set email alerts
|

An Embodied Conversational Agent in an eHealth Self-management Intervention for Chronic Obstructive Pulmonary Disease and Chronic Heart Failure: Exploratory Study in a Real-life Setting

Abstract: Background Embodied conversational agents (ECAs) have the potential to stimulate actual use of eHealth apps. An ECA’s design influences the user’s perception during short interactions, but daily life evaluations of ECAs in health care are scarce. Objective This is an exploratory, long-term study on the design of ECAs for eHealth. The study investigates how patients perceive the design of the ECA over time with regard to the ECA’s characteristics (friend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Our study also found that including any form of visual representation of a CA may be associated with lower attrition rates compared with no visualization at all. This is aligned with many studies on the design of CAs that stressed the importance of design to create positive perceptions of the CA [ 94 ]. However, a recent scoping review reported that visual representation of the CA showed mixed and no association with subjective user experience [ 95 ].…”
Section: Discussionsupporting
confidence: 74%
“…Our study also found that including any form of visual representation of a CA may be associated with lower attrition rates compared with no visualization at all. This is aligned with many studies on the design of CAs that stressed the importance of design to create positive perceptions of the CA [ 94 ]. However, a recent scoping review reported that visual representation of the CA showed mixed and no association with subjective user experience [ 95 ].…”
Section: Discussionsupporting
confidence: 74%
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies are currently looking for new approaches to integrate chatbots and AI‐based conversational agents to support health‐related activities, albeit the quality of content still needs to be improved (Park et al, 2019 ; To et al, 2021 ). While the information was found to be adequate, accessible and useful, nearly all participants felt that the content output could be more concise, accurate and employ appropriate length responses and also include other options to motivate participants to explore other related content at their own pace (Stal et al, 2021 ). One possible explanation for this could be the need of different levels of chatbot personalization (intrinsic, extrinsic or a mix of both) in order to create user profiles or user models and support personalized and adaptative features (Fang et al, 2018 ; Kocaballi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%